2018
DOI: 10.1111/psyp.13281
|View full text |Cite
|
Sign up to set email alerts
|

A high‐density EEG study of differentiation between two speeds and directions of simulated optic flow in adults and infants

Abstract: A high-density EEG study was carried out to investigate cortical activity in response to forward and backward visual motion at two different driving speeds, simulated through optic flow. Participants were prelocomotor infants at the age of 4-5 months and infants with at least 3 weeks of crawling experience at the age of 8-11 months, and adults. Adults displayed shorter N2 latencies in response to forward as opposed to backward visual motion and differentiated significantly between low and high speeds, with sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 90 publications
3
14
0
Order By: Relevance
“…Infants at 9-11 months displayed shorter latencies when compared to prelocomotor infants, and they could differentiate between visual motion speeds. Similar results were found in another study (Vilhelmsen et al 2019), where it was reported that infants at 4-5 months could not differentiate between visual motion speeds and directions, whereas crawling 8-to 11-month-old infants could. The perception of speed develops during the first year of life due to the infant's motor experience (James and Swain 2011), with higher speeds resulting in higher latencies (Kawakami et al 2002).…”
Section: Evoked Responses To Speed Of Motionsupporting
confidence: 90%
See 3 more Smart Citations
“…Infants at 9-11 months displayed shorter latencies when compared to prelocomotor infants, and they could differentiate between visual motion speeds. Similar results were found in another study (Vilhelmsen et al 2019), where it was reported that infants at 4-5 months could not differentiate between visual motion speeds and directions, whereas crawling 8-to 11-month-old infants could. The perception of speed develops during the first year of life due to the infant's motor experience (James and Swain 2011), with higher speeds resulting in higher latencies (Kawakami et al 2002).…”
Section: Evoked Responses To Speed Of Motionsupporting
confidence: 90%
“…Desynchronized activity in all the visual sources was found in response to visual motion in every participant, indicating that underlying neuronal cell assemblies fired in desynchrony, while induced synchronization in the alpha-and beta-bands was found in response to static non-flow, with cells firing in synchrony. Similar desynchronized activity in response to visual motion was found in previous studies (Agyei et al 2016b;Van der Meer et al 2008;Vilhelmsen et al 2019), and is considered to reflect a preparation for information processing (Pfurtscheller 1992), while synchronized activity in response to visual motion reflects a resting state or not-active neuronal assemblies (Pfurtscheller et al 1996).…”
Section: Induced Responses To Visual Motionsupporting
confidence: 80%
See 2 more Smart Citations
“…To focus on oscillatory brain activity in specific frequency bands that has shown to have beneficial effects on learning and memory ( Pfurtscheller and Lopes da Silva, 1999 ), the parietal and central areas were further investigated. These areas have also been associated with cognitive processes in visual perception (e.g., Pfurtscheller et al, 1994 ; Vilhelmsen et al, 2019 ) and language (e.g., Brownsett and Wise, 2010 ; Benedek et al, 2014 ) as well as to be influenced by sensorimotor cortex (e.g., Velasques et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%